Collaborative Governance Pengembangan Desa Wisata Sanankerto dalam Meningkatkan Ekonomi Lokal - Muhammad, Juang Abdi (Jurnal Ilmiah Administrasi Publik, 2021)
The study focused on the process of collaborative governance and supporting and inhibiting factors in order to improve the local economy in the Sanankerto Tourism Village. The tourism potential of Sanankerto Tourism Village is very promising, of course, it can improve the economy of the local residents. However, there are obstacles to management, accessibility, and HR, which have a negative impact on tourism management in Sanankerto Village. This research uses the descriptive qualitative method. Theories used: the process of collaborative governance, the development of tourism villages, tourism, and PEL. The results the collaborative governance process succeeded in bringing changes to the Sanankerto Tourism Village for the better. this success is inseparable from the participation of local communities is a good starting point in the collaborative governance process. This success has led to better local tourism and raised the economy of citizens. Supporting factors of the collaborative governance process: local citizen participation and commitment from the local government and Malang District. Inhibiting factors: lack of tour package socialization, institutional regulations and village tourism do not yet exist.